An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor. Issue 5 (11th January 2016) - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos, T.; Awakowicz, P.; Grundmeier, G.; Devi, A.
Abstract : A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates. Abstract : An efficient plasma-enhanced atomic layer deposition (PE-ALD) process was developed for TiO2 thin films of high quality, using a new Ti-precursor, namely tris(dimethylamido)-(dimethylamino-2-propanolato)titanium(iv ) (TDMADT). The five-coordinated titanium complex is volatile, thermally stable and reactive, making it a potential precursor for ALD and PE-ALD processes. Process optimization was performed with respect to plasma pulse length and reactive gas flow rate. Besides an ALD window, the application of the new compound was investigated using in situ quartz-crystal microbalance (QCM) to monitor surface saturation and growth per cycle (GPC). The new PE-ALD process is demonstrated to be an efficient procedure to deposit stoichiometric titanium dioxide thin films under optimized process conditions with deposition temperatures as low as 60 °C. Thin films deposited on Si(100) and polyethylene-terephthalate (PET) exhibit a low RMS roughness of about 0.22 nm. In addition, proof-of-principle studies on TiO2 thin films deposited on PET show promising results in terms of barrier performance with oxygen transmission rates (OTR) found to be as low as 0.12 cm 3 × cm −2 × day −1 for 14 nm thin films.